2015
DOI: 10.1590/1516-635x1702199-208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fennel (Foeniculum Vulgare Mill.) Used as a Feed Additive on The Egg Quality of Laying Hens Under Heat Stress

Abstract: Keywords Fennel, heat stress, laying hens, antioxidant, feed.Submitted: March/2014 Approved: November/2014 ABSTRACT In this study, one hundred and twenty 40-wk-old White Leghorn laying hens were submitted to two different thermal conditions (24° C vs. 34° C) and were fed three levels (0, 10, or and 20 g/kg of diet) of fennel fruits (Foeniculum vulgare Mill.) as a feed additive in. This study was carried out according to a factorial design consisting of two temperatures and three fennel levels with five 5 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…A tendency toward higher body weight gain was recorded in the red pepper group, followed by black cumin and fennel supplemented groups compared with control. Lokaewmanee et al., 2013 , Khan et al., 2013 and Gharaghani et al. (2015) reported that the production performance of laying hens was not changed with dietary inclusion of red pepper, black cumin or fennel, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tendency toward higher body weight gain was recorded in the red pepper group, followed by black cumin and fennel supplemented groups compared with control. Lokaewmanee et al., 2013 , Khan et al., 2013 and Gharaghani et al. (2015) reported that the production performance of laying hens was not changed with dietary inclusion of red pepper, black cumin or fennel, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Research on fennel leaves and fruits revealed that its essential oil possesses antioxidant, antimicrobial, and hepatoprotective functions ( Özbek et al., 2003 , Gende et al., 2009 , Shahat et al., 2011 ). Dietary inclusion of fennel in laying hen diets was shown to alleviate the negative effects of heat stress on egg quality parameters ( Gharaghani et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fennel also has strong antiviral, antimicrobial, and anti-inflammatory effects, which may improve gut health and eliminate pathogens. It was reported that the FSP is a rich source of essential oil (anethole, fenchone, methyl chavicol, limonene, phellandrene, camphene, pinine, anisic acid, and palmitic, oleic, linoleic, and petroselenic acids, volatile compounds, flavonoids, phenolics [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that FSP had no adverse effects on carcass traits. Moreover, phytogenic plants and their essential oils are used as preservation approaches to enhance the sensory attributes and prolong the shelf life of animal products [19,21,36,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation